Tax Evasion: Faktor-Faktor Yang Mempengaruhinya Menurut Persepsi Wajib Pajak - Nur Kholis; Lintang Kurniawati (Department of Accounting-Faculty of Economic and Business (FEB), 2022)
that are used for national development and also the community’s economy. People’s non-compliance in carrying out their tax obligations has long been in the spotlight in Indonesia.The purpose of this study is to provide empirical evidence about the factors that influence the perception of MSME taxpayers in committing tax evasion using the variabels of Justice, Tax Sanctions, Taxation System, Disobedience Attitudes, and Discrimination Attitudes. Using 60 sample of taxpayers of Small and Medium Enterprises in Sukoharjo by sampling using random sampling of taxpayers registered at KPP Pratama Sukoharjo and using the SPSS 25 analysis tool. The results showed that the variabel of justice, tax sanctions, taxation system, taxpayer disobedience had a positive and significant effect on Tax evasion and Discrimination Attitudes had a negatif and significant effect on Tax evasion for Small and Medium Enterprises taxpayers.